Antimicrobial Activity of Terminalia sericeae Burch. exDC. - Rama Devi, D.; Lakshmi, P.; Ganapaty, S. (Asian Journal of Chemistry, 2010)
The methanolic extract of the leaf and bark of Terminalia sericeae was tested for antimicrobial activity on Staphylococcus aureus, Staphylococcus subtilis, Streptococcus mutans, Streptococcus anginosus, Lactobacillus acidophilus, Micrococcus luteus, Bacillus subtilis, Escherichia coli, Erwinia, Enterobacter aerogenus, Klebsiella pneumoniae, Proteus vulgaris, Pseudomonas aerginosa and fungai are Rhizopus, Aspergillus niger, Saccharomyces cerenesiae, Mucor, Rhizoctonia solanic, Candida albicans and Pencillium chrysogenum at 100, 300 and 500 mg/kg dose levels. Both the extracts showed considerable activity. For testing, Agar cup plate method was used and chloramphenicol (10 mg/mL) and fluconazole (1 mg/mL) as standards.